Care work : dreaming disability justice - Piepzna-Samarasinha, Leah Lakshmi, 1975- (Arsenal Pulp Press, 2018)
"Leah Piepzna-Samarasinha is a poet and essayist whose most recent book, the memoir Dirty River, was a finalist for a Lambda Literary Award and the Publishing Triangle's Judy Grahn Award for Lesbian Nonfiction. She is also a long-time member of the disability justice movement, which advocates for the rights of the disabled. In her latest book of essays, Leah writes passionately and personally about disability justice, on subject such as the creation of care webs, collective access, and radically accessible spaces. She also imparts her own survivor skills and wisdom based on her years of activist work, empowering the disabled--in particular, those in queer and/or BIPOC communities--and granting them the necessary tools by which they can imagine a future where no one is left behind. Presently, disability justice and emotional/care work are buzzwords on many people's lips, and the disabled and sick are discovering new ways to build power within themselves and each other; at the same time, those powers remain at risk in this fragile political climate in which we find ourselves. Powerful and passionate, Care Work is a crucial and necessary call to arms. "--